Model struktur amalan terbaik faktor kejayaan kritikal sistem pengurusan kualiti projek pembinaan - Shaari, Nursyamimi (2019)
Six Critical Success Factors (CSFs) for the implementation of a Project Quality Management System (PQMS) have been determined according to previous surveys. The PQMS’s CSFs include client’s commitment, integration of quality plan, measurement and improvement, education and training, teamwork and communication, and use of information and communication technology (ICT). However, implementation of PQMS is still considered not encouraging when a number of issues such as lack of commitment from stakeholders, lack of teamwork and communication among the parties involved, lack of training and learning, uncertainty in the plans qualities involved, and voluminous of documentations still occur. These problems are augmented by lack of knowledge and skills as well as the absence of a comprehensive guide to implement PQMS. Therefore, to address these problems, a set of best practices to implement PQMS’s CSF was established through the formulation of three related objectives: 1) Determine the practices for each of PQMS’s CSF; 2) Determine the project success criteria that have a positive impact with the implementation of PQMS; and 3) Study the relationship between the practices for PQMS’s CSF and criteria for project success to form a set of best practices. The study was conducted using two methods, which was an interview with an expert to verify the elements formulated in the questionnaire and distribution of the questionnaire. Initially, 31 practices and 10 project success criteria were identified through literature review followed by interviews conducted with experts. An addition of two practices were included in the list making it 33 practices but the project success criteria remain the same. Then, the questionnaires were distributed to 500 Grade 7 contractors registered with the Construction Industry Development Board (CIDB) in Peninsular Malaysia. However, 275 were returned and only 223 were completed and accepted to analyze for this research. Then, the data were analyzed using descriptive analysis and relative importance index (RII) to achieve objectives 1 and 2, and SEM-PLS was used to achieve objective 3. The findings of the study showed that 28 of 33 practices have been identified to implement PQMS’s CSF. In the meantime, only nine of ten criteria had positive impacts with the implementation of PQMS. Thus, these findings have shown that 25 of 33 practices were determined as best practices to successful implement PQMS’s CSF in construction. These best practices can be viewed as a new contribution to the body of knowledge by being the basis as well as reference for academics and industry to ensure that construction process will be efficient in the future.